2015
DOI: 10.1161/circoutcomes.114.001545
|View full text |Cite
|
Sign up to set email alerts
|

Association of Smoking Status With Angina and Health-Related Quality of Life After Acute Myocardial Infarction

Abstract: Background Smoking cessation after acute myocardial infarction (AMI) decreases the risk of recurrent AMI and mortality by 30–40%, but many patients continue to smoke. The association of smoking with angina and health-related quality of life (HRQOL) after AMI is unclear. Methods and Results Patients in 2 U.S. multicenter AMI registries (n=4003) were assessed for smoking and HRQOL at admission and 1, 6 and 12 months after AMI. Angina and HRQOL were measured with the Seattle Angina Questionnaire (SAQ) and Short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 47 publications
3
19
0
5
Order By: Relevance
“…Critchley et al reviewed 20 studies with 12,603 smoking patients with ischemic heart disease in a meta-analysis and documented that cessation of smoking after acute myocardial infarction or cardiac surgery could significantly reduce mortality [24]. Buchanan et al evaluated the association of smoking status with angina and HRQOL after acute myocardial infarction (AMI) and found that smokers who quitted after AMI had similar angina levels and mental health as non-smokers [25]. In our study, about 42.3% of smokers quitted after DES implantation, who have demonstrated significantly better improvement in HRQOL than persistent smokers and comparable improvement with nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…Critchley et al reviewed 20 studies with 12,603 smoking patients with ischemic heart disease in a meta-analysis and documented that cessation of smoking after acute myocardial infarction or cardiac surgery could significantly reduce mortality [24]. Buchanan et al evaluated the association of smoking status with angina and HRQOL after acute myocardial infarction (AMI) and found that smokers who quitted after AMI had similar angina levels and mental health as non-smokers [25]. In our study, about 42.3% of smokers quitted after DES implantation, who have demonstrated significantly better improvement in HRQOL than persistent smokers and comparable improvement with nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that smoking can induce oxidative stress and elevated RDW is correlated with the number of cigarettes smoked per day as well as duration of smoking [ 100 , 101 ]. Smoking has been also proved to be a well-known risk factor in MI [ 102 ]. A study has identified the stronger association between RDW and MI among smokers, which exactly supports the hypothesis that RDW level can reflect the inflammation status [ 24 ].…”
Section: Mechanismsmentioning
confidence: 99%
“…The DNA amplicons were analyzed on automated pyrosequencing device PSQTMHS96MA (Biotage, Sweden) [10,11] . Primers for pyrosequencing are listed in Table 2 [ [13][14][15][16]20] .…”
Section: Methodsmentioning
confidence: 99%
“…One of the main risk factors for cardiac angina is a atherosclerosis of coronary arteries [2][3][4][5][6] . Other risk factors for cardiac angina include hypertension, diabetes mellitus, obesity, smoking; stress, hypodynamia, infectious diseases, allergic lesions and genetic mutations [7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%